Simulations of the star-forming molecular gas in an interacting M51-like galaxy: cloud population statistics - Treß, Robin G.; Sormani, Mattia C.; Smith, Rowan J.; Glover, Simon; Klessen, Ralf S.; Mac Low, Mordecai-Mark; Clark, Paul C.; Duarte-Cabral, Ana (Monthly notices of the Royal Astronomical Society, 2021)
To investigate how molecular clouds react to different environmental conditions at a galactic scale, we present a catalogue of giant molecular clouds (GMCs) resolved down to masses of ∼10 M⊙ from a simulation of the entire disc of an interacting M51-like galaxy and a comparable isolated galaxy. Our model includes time-dependent gas chemistry, sink particles for star formation, and supernova feedback, meaning we are not reliant on star formation recipes based on threshold densities and can follow the physics of the cold molecular phase. We extract GMCs from the simulations and analyse their properties. In the disc of our simulated galaxies, spiral arms seem to act merely as snowplows, gathering gas, and clouds without dramatically affecting their properties. In the centre of the galaxy, on the other hand, environmental conditions lead to larger, more massive clouds. While the galaxy interaction has little effect on cloud masses and sizes, it does promote the formation of counter-rotating clouds. We find that the identified clouds seem to be largely gravitationally unbound at first glance, but a closer analysis of the hierarchical structure of the molecular interstellar medium shows that there is a large range of virial parameters with a smooth transition from unbound to mostly bound for the densest structures. The common observation that clouds appear to be virialized entities may therefore be due to CO bright emission highlighting a specific level in this hierarchical binding sequence. The small fraction of gravitationally bound structures found suggests that low galactic star formation efficiencies may be set by the process of cloud formation and initial collapse.